Tyendinaga tweet ids - Ruest, Nick
80,264 tweet ids for Tyendinaga tweets, collected with Documenting the Now's twarc. Tweets can be “ rehydrated ” with Documenting the Now’s twarc , or Hydrator. twarc hydrate tyendinaga-20210115-ids.txt > tyendinaga.jsonl. Tweets were collected via the Standard Search API on a cron job every five days beginning on February 24, 2020. Collection is ongoing. The account that was used to collect these Tweets failed to collect Tweets for the period from Sun Jul 26 03:46:41 +0000 2020 through Fri Aug 07 20:33:27 +0000 2020.